A multi-layer protection scheme for MMC-power electronic transformers - Xinchen Zhu; Niancheng Zhou; Jianquan Liao; Qianggang Wang; Yongjie Luo; Dachuan Yu (International Journal of Electrical Power & Energy Systems)
As a key interfacing equipment for the AC-DC hybrid distribution network, power electronic transformers (PETs) lack a protection scheme with high sensitivity and reliability. To address this issue, this paper proposes a multi-layer protection scheme for modular multilevel converter-power electronic transformers (MMC-PETs). Firstly, the fault characteristics and fault propagation mechanisms of various MMC-PET faults are analysed. On this basis, this study deconstructs MMC-PET into three layers and constructs criteria for each layer of protection. Among them, the two supplementary protection layers are introduced to improve protection sensitivity for faults inside MMC-PET. And the protection for faults outside MMC-PET can remain unaffected by the suppression of negative sequence currents during AC-side faults. Finally, a 10 kV/380 V MMC-PET is modelled in MATLAB/Simulink and RT-LAB real-time simulation platform, and the effectiveness of the proposed protection scheme is verified via simulation results.